Career Development Interventions in Secondary Schools in the State of Terengganu, Malaysia - Mat Rashid, Abdullah; Bakar, Ab. Rahim; Asimiran, Soaib; Tieng, Loh Pei (Eurojournals, 2009)
Changes in the economy have altered the requirements for both college and work, with important implication for career interventions in school with aim to provide information and guidance to students with regard to personal, academic and career option (Rosenbaum & Person, 2003). Career development intervention is defined as any activity that empowers people to cope effectively with career development tasks (Niles & Harris-Bowlsbey, 2002). Unfortunately, no uniform structure, definition, and organization of these interventions exits in Malaysia school system. Without the knowledge of such structure, real progress in career development interventions research and practice will be severely circumscribed or absent. This study was conducted with aim to identify the comprehensive list of career development interventions in secondary schools in Terengganu. Through interview sessions with school counselors, a comprehensive list containing 27 intervention programs were found. These 27 interventions were divided into four categories which are work-based interventions, advising interventions, introductory interventions and curriculum based interventions.